Effects and Consequences of International Law on the International Monetary Fund - Abdullah, Amer Hadi; Abdulmajeed, Eman Naji; Al-Bayati, Adnan Khalil Kazem; Al-Obaidi, Bushra Salman Husain (Journal of Ecohumanism, 2024)
Background: The International Monetary Fund (IMF) is a critical organization in global financial governance, providing monetary aid and policy guidance to member countries. Although frequently seen as primarily commercial, its functions are nevertheless profoundly linked to international law. Objective: This article aims to determine the impact and repercussions of international law on the IMF's operations, policies, and member-state relations. Methods: The article examines the main sources of international law, IMF agreements, and IMF contacts with member governments during the previous 30 years. Legal practitioners and key stakeholders were interviewed to supplement our data gathering and analysis. Results: The current study reveals that international law significantly impacts IMF policy recommendations, funding conditions, and dispute resolution procedures. Trouble arises when the Fund's recommendations conflict with international law, especially in sovereign debt and human rights. Conflicts may make member states doubt the IMF's legitimacy, claiming it violates international law. Conclusion: While the IMF acts primarily within an economic framework, it is closely linked to international law. Addressing obvious gaps and establishing consistency between the IMF's practices and international legal requirements is critical for the IMF's sustained credibility and effective functioning in the global financial architecture.